Rapid and direct detection of herpes simplex virus type 1 and type 2 by Real-Time PCR method in clinical specimens - Masoomeh Rezanezhadi; Fahimeh Azadi; Shayan Marhamati; Hamid Reza Joshaghani (Medical Laboratory Journal, 2023)
Background: Herpes simplex viruses (HSV-1 and HSV-2) are a common cause of dermal, oral, and genital infections worldwide. Rapid diagnosis of infected patients will prevent transmission to uninfected individuals. Therefore, this study aimed to detect HSV-1 and HSV-2 by real-time polymerase chain reaction (RT-PCR) in patients from Golestan, Iran. Methods: In this cross-sectional study, 645 suspected HSV patients hospitalized in the health centers of Golestan Province were selected between 2015 and 2020. Demographic data were collected, and DNA was extracted from the samples. Detection of HSV-1 and HSV-2 was performed by RT-PCR. Results: Of the 645 samples tested by RT-PCR, 9 samples (1.39 %) were found to be positive for HSV-1/HSV-2, and the rest of the samples (98.6%) were negative. Of the 9 positive samples, 8 cases (88.8%) were HSV-1, of which 7 cases (77.7%) were from the cerebrospinal fluid (CSF) and 1 case (12.5%) from the vagina. HSV-2 was seen only in 1 vaginal specimen (11.1%). Conclusion: Early diagnosis of these viral infections is very important as it can lead to early treatment and avoid further symptoms and even death. Thus, molecular approaches can provide an option for quicker diagnosis.